ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN - Isselia Naftali Erfiyanto, 12.05.52.0130; Nurhayati, Ida (Students Journal of Economic and Management, 2016)
This study aimed to examine the effect of the board of directors, independent directors, audit committee, managerial ownership, institutional ownership on the financial performance.Populasi in this study are all real estate and property company listed in Indonesia Stock Exchange 2008-2014. The sampling technique was conducted by purposive sampling. Based on purposive sampling of 115 companies obtained before and after the outlier in the outlier sample as many as 109 companies for 7 years. Data analysis technique used is multiple linear regression analysis. The results of this study indicate that the Board of Directors, the Independent Commissioner does not significantly influence the direction of affairs negatively affect financial performance. Institutional ownership not significant positive correlation with the direction of the Financial Performance.The Audit Committee significant influence with a positive correlation to the direction of Financial Performance. Managerial Ownership significantly influence the direction of a negative relationship to the Financial Performance. Keywords: board of directors, independent directors, audit committee, managerial ownership, institutional ownership and financial performance.